Pengaruh Strategi Pemasaran Mie Instant Gaga Mie 100 pada PT Jakarana Tama - Nurbekti Aji Hawatri; Mirzam Arqy Ahmadi (Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of marketing strategies on the product performance of Gaga Mie 100 at PT Jakarana Tama. The method used is a literature review, which involves reviewing various relevant secondary sources, such as scientific journals, articles, and research reports. The focus of the research includes elements of marketing strategy, namely product, price, promotion, and distribution. The results show that product innovation and digital promotion play a significant role in increasing brand awareness and consumer purchasing interest. Competitive prices attract the attention of lower-middle consumer segments, while extensive distribution ensures the availability of products in the market. However, some challenges still need to be addressed, such as improving the effectiveness of distribution in rural areas and continuing to present product innovations in line with market trends. The conclusion of this study confirms that a holistic and adaptive marketing strategy is key to the success of Gaga Mie 100 in a competitive market. PT Jakarana Tama is advised to strengthen digital promotions, expand distribution networks, and conduct ongoing evaluations of marketing strategies to maintain product competitiveness.